A Critical Investigation of the Impact of Religiosity, Perception towards Facility, Service Quality, and Tax Rebate on Compliance Behavior of Income Zakat - HAJI-OTHMAN, YUSUF; YUSUFF, MOHD SHOLEH SHEH; ABDULLAH, NORHAYATI (The journal of contemporary issues in business and government, 2021)
Despite a religious decree on the compulsory position of zakat on employment income in Malaysia, many Muslims still fail to fulfill their religious obligation to pay income zakat. The Office of the Secretary of the State of Kedah (SUK) has directed Muslim public servants who have fulfilled the conditions of perfect title, nisab, and hawl to pay zakat to Kedah State Zakat Board through a monthly salary deduction scheme. However, some Muslim public educators working in Kedah are not compliant with the directive. Furthermore, the studies so far have provided mixed and inconclusive evidence regarding the factors that determine the income zakat compliance behavior. Therefore, this study critically investigates the impact of religiosity, perception towards facility, service quality, and tax rebate on compliance behavior of income zakat in Kedah, Malaysia. This study employs a quantitative method using questionnaires to determine significant determinants of compliance behavior of income zakat. This study provides empirical evidence that religiosity, perception towards facility, service quality, and tax rebate are significant determinants of compliance behavior of income zakat in Kedah. This study strives to provide evidence that could be used as guidance for suitable policy and measures by Kedah State Zakat Board to improve zakat collection in the future.